Corneal ulceration in South East Asia. II: A strategy for the prevention of fungal keratitis at the village level in Burma. Issue 8 (17th May 2006) - Maung, N; Thant, C C; Srinivasan, M; Upadhyay, M P; Priyadarsini, B; Mahalakshmi, R; Whitcher, J P
Abstract : Aim: To prove that topical antifungal and antibiotic prophylaxis distributed by grass roots village health workers (VHWs) in Burma is an effective public health intervention for the prevention of post-traumatic microbial keratitis in a population where the majority of ulcers are fungal. Methods: Three villages in Bago District with a combined population of 16 987 were selected for the study. This defined population was followed prospectively for 12 months by 15 VHWs who were trained to identify post-traumatic corneal abrasions with fluorescein dye and a blue torch and to administer 1% chloramphenicol and 1% clotrimazole ointment three times a day for 3 days to the eyes of individuals who fulfilled the eligibility criteria. Results: During the 12 month period 273 individuals reported to VHWs with an ocular injury and 126 were found to have a corneal abrasion. All 126 were treated with 1% chloramphenicol and 1% clotrimazole ointment three times a day for 3 days, and all healed without sequelae. Conclusions: Both fungal and bacterial ulcers that occur following traumatic corneal abrasions can be effectively prevented in a village setting by using relatively simple measures that local volunteer public health workers can easily be taught to employ.